Islamic Banking In Malaysia: The Journey So Far - Balarabe, Abubakar; Abdullah, Md. Faruk; Gwadabe, Uzairu Muhammad; Muhammad, Auwal Jibril (Adpebi Science Series, 2022)
The study aims to review in general the historical context of Islamic banking from the beginning of the Islamic era to the establishment of Islamic banking in Malaysia. The Islamic banking system in Malaysia has gradually developed and succeeded in line with countries such as Dubai, Saudi Arabia, Indonesia, the United Kingdom, and Kuwait, which are countries that should be ahead of Malaysia. This study aims to review the Malaysian history of Islamic banking and finance. The development of Islamic banking in Malaysia successful Islamic banking and finance products and services. Also, the issues and challenges and prospects of Islamic banking. The research methodology is qualitative, and data has been collected from various sources such as libraries, documents, articles, the Internet, books, banking websites, and literature related to the history of Islamic banking. The study shows that Malaysia is among the best places in the world to practice Islamic banking, as it offers universities, institutions, sectors and seats for specialists in Islamic law and Islamic banking. The newspaper revealed that Malaysia is currently the financial technology for Islamic banking and finance. The study's results show that Islamic banking has come a long way toward becoming a profitable and globally competitive alternative to the current banking system.